Freedom, reason and education in J. Ortega y Gasset - Serafín Martín Tabernero del Río (FahrenHouse, 2009)
This work tray of the relationship of liberty whit raison and education, accor- ding J. Ortega y Gasset. So the qualities or categories of the human life, as biography, are shows: one of these is the liberty. This is thought as not subjected condut to instintives ways. And it is that the life is given us not done; but we have that do her with succesives elections in all possi- bilities of action of each moment. From that it follows that how more developed is the raison of the man so much better he will do the task of choosing. Thereby it is seen the importance that the education has for the human liberty.